Kerapatan Jenis Lichenes Di Sekitar Kawah Sikidang Pegunungan Dieng (Density of Lichens Arround Sikidang Creater of Dieng Plateau) - Widodo, Edy; Utami, Sri (JURNAL SAINS DAN MATEMATIKA, 2007)
ABSTRACT---Lichens are symbiotic plant composed of two different types of organisms i.e. fungi and algae. Lichens sensitive to air pollutan of sulfur dioxide (SO2). Sikidang creater are still active to emist off SO2 and will be affected the availability of lichens as well as the their individual density along SO2 gradient. Sampling of lichens taken with sistematic method. Point sampling four were taken along transect line and sample plot 5 m x 5 m in size was applied..The occurance of species and density was record in every sampling plot. The environment factor measured were air SO2, pH, moisturized and air temperature. There were three species of lichens in Sikidang Creater, those are Cladonia beaumontii, Dactylina artica abd Parmelia cumberlandia. The highets density of species lichens is Cladonia beaumontii. Â  Keywords : density, Lichens. Sikidang Creater